Factors Affecting Stunting in Toddlers in the Working Area of the UPTD Puskesmas Deleng Pokhisen Aceh Tenggara - Syamsir, Wira Presty; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (PROMOTOR, 2025)
Background: Stuntingis a condition of failure to thrive in children under five years old (babies under five years) resulting from chronic malnutrition so that the child is too short for his age. Stunting has the potential to slow down brain development, with long-term impacts in the form of mental retardation, low learning ability, and the risk of developing chronic diseases such as diabetes, hypertension, and obesity. The aim of this research is to determine and analyze the factors that influence stunting in toddlers in the UPTD Puskemas Deleng Pokhisen Aceh Tenggara. Research Method: This research uses quantitative methods with a cross sectional design and sampling using total sampling. The population and research sample were 210 respondents, namely mothers who had stunted toddlers. This research uses a questionnaire. The research time is June - July 2024. This research analysis uses Univariate, Bivariate and Multivariate. The statistical tests used are the chi-square test and logistic regression. Research Results: Research results regarding the influence of maternal height p value= 0.006, history of diarrheal disease p value= 0.049, family income p value= 0.003, diet p value= 0.001 with stunting in toddlers. Based on the results of the logistic regression test, the most influential variable was a history of diarrhea with an Exp(B) value of 2.769. Conclusion: The conclusion in this study is that there is an influence on maternal height, history of diarrhea, family income, and eating patterns on stunting among toddlers in the UPTD Puskemas Deleng Pokhisen Aceh Tenggara. In order to reduce the prevalence of stunting in toddlers, it is hoped that the Health Service, Community Health Centers, especially health workers, will collaborate to increase health promotion about stunting, the risk of diarrheal disease due to stunting, the benefits of family income and the importance of a good diet for toddlers.